A fresh look at environment friendly customer's profile: evidence from India. (5th October 2020) - Patharia, Ishani; Rastogi, Sanjay; Vinayek, Ravinder; Malik, Sheetal
Increasing environmental concern has led to global pressure on companies to produce environment friendly products. There is a corresponding need to improve environment friendly purchase behaviour. This paper provides a precise profile of environment friendly customers of electronic products by performing logistic regression analysis. Data was collected from 589 Indian customers who had purchased electronic products during the six months before participating in the survey. The results reveal that people with high environmental concern, having good knowledge about environmental problems and their solutions through environment friendly buying behaviour will buy environment friendly electronic products if they have trust in product attributes and believe that their actions contribute towards environmental sustainability. These findings provide very important clues to design pragmatic strategies to improve environment friendly purchase behaviour.